Nanoparticles of Rh confined and tailored by LaFeO3–La2O3 on SiO2 for direct ethanol synthesis from syngas. Issue 13 (11th June 2019) - Zhong, Huixian; Wang, Jiaming; An, Kang; Fang, Kegong; Liu, Yuan
Abstract : A catalyst with a novel composition for direct ethanol synthesis from syngas was prepared and investigated in this work, which is Rh nanoparticles (NPs) highly dispersed on La2 O3 modified LaFeO3, and the Rh NPs/La2 O3 –LaFeO3 was loaded on SiO2 with high surface area. Abstract : A catalyst with a novel composition for direct ethanol synthesis from syngas was prepared and investigated in this work, which is Rh nanoparticles (NPs) highly dispersed on La2 O3 modified LaFeO3, and the Rh NPs/La2 O3 –LaFeO3 was loaded on SiO2 with high surface area. The catalyst was prepared by using LaFe1− x Rh x O3 in the perovskite phase as the precursor, which was transformed to Rh/La2 O3 –LaFeO3 /SiO2 after reduction. The results showed that, compared to Rh–La2 O3 /SiO2, the activity and selectivity to ethanol were improved markedly, which was ascribed to the well-matched catalyzing process by the active sites of Rh 0, Rh + (or Rh δ + ) and the oxygen vacancies on the surface of LaFeO3 ; of those, Rh 0 dissociatively adsorbed CO and the latter two associatively adsorbed CO. Moreover, the interaction of La2 O3 and LaFeO3 donated electrons to rhodium, which effectively adjusted the ratio of CO adsorbed associatively and dissociatively, and thus improved the selectivity to ethanol and lowered the selectivity to methanol. The catalyst also exhibited excellent resistance to the sintering of Rh NPs and to carbon deposition, which was attributed to the confinement of Rh NPs by La2 O3 and LaFeO3, the eliminating effect of La2 O3 and LaFeO3 and the very high dispersion of Rh NPs.